Mindfulness reduces avaricious monetary attitudes and enhances ethical consumer beliefs: mindfulness training, timing, and practicing matter - Gentina, Élodie (Journal of business ethics, 2021)
Mindfulness-the awareness of the present moment and experiences in daily life-contributes to genuine intrinsic and social-oriented values and curbs materialistic and hedonistic values. In the context of materialism, money is power. Avaricious individuals take risks and are likely to engage in dishonesty. Very little research has investigated the effects of mindfulness in reducing the avaricious monetary attitudes and enhancing ethical consumer beliefs. In this study, we theorize that mindfulness improves consumer ethics directly and indirectly by lowering avaricious monetary attitudes. To test our theory, we collected data from 523 individuals with the Mindfulness-Based Stress Reduction (MBSR) training and 307 individuals without MBSR. The results of our whole sample (N = 830) support our theory. Three multiple-group confirmatory factor analyses (MGCFAs) reveal intriguing discoveries. First, with MBSR training, mindfulness excites consumer ethical beliefs directly and indirectly. Without training, trait mindfulness fails to reduce monetary attitudes—mindfulness training matters. Second, the power of MBSR training holds for participants completing the training within 1 year, but wears off after 1 year—the duration after training matters. Finally, after 1 year, the training retains its strength for those who practice mindfulness, but weakens its power for those who do not—practice matters. We shed light on mindfulness, monetary wisdom, and consumer ethics, in particular, and business ethics, in general.